Protection of youth rights: the role of Human Right Commission of Malaysia (SUHAKAM) - Azhar, Alias; Yeon, Asmah Laili; Ayub, Zainal Amin; Arshad, Rozita (MAXWELL Science Publication, 2016)
Malaysia introduced Youth Societies and Youth Development Act 2007 (YSYDA 2007) and gazetted in July 2007.It is an Act to facilitate the development of youth in Malaysia from the aspect of education, research and human resource. Therefore, this study aims to examine efforts of the Human Rights Commission of Malaysia (SUHAKAM) as a National Human Rights Institution (NHRI), play an important role in the mainstream of the efforts to ensure the protection and promotion of youth rights.This study is totally a qualitative research study in which it is more exploratory in nature and possibly resulting in the development of concepts and theories. This study also used historical and interview approach as to find out how and why SUHAKAM have come to take their present form.In addition, this study also summarizes the efforts and roles played by the SUHAKAM pursuant to protect of youth rights.